2005
DOI: 10.1002/bip.20349
|View full text |Cite
|
Sign up to set email alerts
|

Thermally induced coil‐to‐helix transition of sodium gellan gum with different molar masses in aqueous salt solutions

Abstract: Using 5 samples of well-purified Na-gellans (Na-gellans G1-G5, weight-average molar mass M(w) = 120 x 10(3)-32 x 10(3) at 40 degrees C), the effects of molar mass on the coil-to-double-helix transition in aqueous solutions with 25 mM NaCl were studied by light scattering and circular dichroism (CD) measurements, viscometry, and differential scanning calorimetry (DSC). From the temperature dependence of M(w), molar ellipticity at 201 nm [theta]201, intrinsic viscosity [eta], and DSC exothermic curves, it was fo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
14
0

Year Published

2007
2007
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 23 publications
(14 citation statements)
references
References 54 publications
0
14
0
Order By: Relevance
“…Although the intrinsic viscosity for the released chains is far lower than that for the mixture, the difference in the intrinsic viscosity is not enough significant to induce the difference in the helix-coil transition temperature as was reported previously. 31,32 Effect of Added Salts on the Release of Gellan Chains Figure 7 shows the dependence of the release ratio, q, on the KCl and CaCl 2 concentration in the external solution, C s , for C g ¼ 3:0% (w/w) at 10 C. In the case of the external solutions with added KCl, the q values were almost independent of changes in C s in the range 0.10 mmol kg À1 C s 1.0 mmol kg À1 , and they were almost equal to the value obtained in the case of distilled water (square symbol). A marked decrease in the q values was observed in the range 1.0 mmol kg À1 < C s 100 mmol kg À1 .…”
Section: Coil-helix Transition Temperaturesmentioning
confidence: 99%
See 1 more Smart Citation
“…Although the intrinsic viscosity for the released chains is far lower than that for the mixture, the difference in the intrinsic viscosity is not enough significant to induce the difference in the helix-coil transition temperature as was reported previously. 31,32 Effect of Added Salts on the Release of Gellan Chains Figure 7 shows the dependence of the release ratio, q, on the KCl and CaCl 2 concentration in the external solution, C s , for C g ¼ 3:0% (w/w) at 10 C. In the case of the external solutions with added KCl, the q values were almost independent of changes in C s in the range 0.10 mmol kg À1 C s 1.0 mmol kg À1 , and they were almost equal to the value obtained in the case of distilled water (square symbol). A marked decrease in the q values was observed in the range 1.0 mmol kg À1 < C s 100 mmol kg À1 .…”
Section: Coil-helix Transition Temperaturesmentioning
confidence: 99%
“…3.5 assuming that ¼ 1:3 and that the value is independent of the type of counter ion and salt concentration added. Ogawa et al 31,32 studied the effect of molecular weight on the conformational change of sodium type gellan molecules, and found that a gellan molecule does not form a helix if the molecular weight is lower than 17,000.…”
mentioning
confidence: 99%
“…However, the gelation is greatly affected by the chemical nature of the cations present, being stronger with divalent ones. The rheological and physical properties of GG have been widely investigated [27-30]. Recently, Masakuni et al .…”
Section: Introductionmentioning
confidence: 99%
“…There have been several methods used previously to characterize gellan gum, including rheology, light scattering, nuclear magnetic resonance (NMR) spectroscopy, and dichroism spectroscopy. [3][4][5][6][7] These methods have been used to characterize the conformational transition from a random coil to a doublehelix structure (twice higher molecular weight) on cooling. In one instance, the molecular weight of the gellan gum was varied by sonication (the only information given on the sonication was the resulting intrinsic viscosity of the samples).…”
Section: Introductionmentioning
confidence: 99%